Harapan Membayar Benda Budaya Kulit Kerang (Kigi) di Kabupaten Intan Jaya - Selvina Kobogau (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
The aim of the research is to identify the economic value of the Shell Shell (Kigi) of the Migani tribe, research location in Gamagae Village, Intan Jaya Regency. Classified as a type of basic research, the technique for determining respondents was chosen based on non-probability sampling (purposive judgment) and the population was homogeneous in terms of their knowledge about Kigi. The research data analysis method uses Willingness to pay (WTP) to determine the expected value of the rupiah unit as the maximum value desired by consumers/society to obtain the optimal benefit value of Kigi cultural objects. The conclusion of this research is that the expected economic Willingness to Pay (WTP) value of seashells (Kigi) in Intan Jaya Regency, as a cultural object, provides recognition of the optimal benefits of "social status" rather than the benefits of "economic status" needs.